Nitrogen fixing bacteria, Azotobacter sp. in aquatic sediment - P., Lakshmanaperumalsamy (Fishery Technology, 2021)
Non-symbiotic, free living, nitrogen fixing bacteria, Azotobacter sp. was estimated in sediments of estuarine, marine, backwater and mangrove environments of Portonovo. Number of colony forming units (CFU) of Azotobacter sp. was less (5 to 27 cells/g of dry sediment). CFU of total heterotrophic bacteria (THB), actinomycetes and fungi were between 4.1x10 super(6) and 4.5x10 super (7), 0.8x10 super(5) and 4.9x10 super(5), 1.1x10 super(5) and 3.8x10 super(5)/g respectively. Mangrove sediments contained more CFU of the above microbial groups.